2010
DOI: 10.5194/hessd-7-1-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Integrated response and transit time distributions of watersheds by combining hydrograph separation and long-term transit time modeling

Abstract: Abstract. We present a new modeling approach analyzing and predicting the Transit Time Distribution (TTD) and the Response Time Distribution (RTD) from hourly to annual time scales as two distinct hydrological processes. The model integrates Isotope Hydrograph Separation (IHS) and the Instantaneous Unit Hydrograph (IUH) approach as a tool to provide a more realistic description of transit and response time of water in catchments. Individual event simulations and parameterizations were combined with long-term b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 32 publications
(23 reference statements)
2
43
2
Order By: Relevance
“…In forested headwaters, trees not only affect the amount of 58 spatiotemporal throughfall (Gerrits et al, 2010) and isotopic composition (Allen et al, 2015), but 59 also affect the subsurface connectivity (Weiler et al, 1998). Interception and transpiration of 60 trees together with higher infiltration capacities of the soils can have a delaying effect on stream 61 response, and pre-event water dominates the stormflow (Buttle, 1994; Klaus and McDonnell, 62 2013;Roa-García and Weiler, 2010). Roa-García and Weiler (2010) observed higher pre-event 63…”
Section: Introduction 29mentioning
confidence: 99%
See 1 more Smart Citation
“…In forested headwaters, trees not only affect the amount of 58 spatiotemporal throughfall (Gerrits et al, 2010) and isotopic composition (Allen et al, 2015), but 59 also affect the subsurface connectivity (Weiler et al, 1998). Interception and transpiration of 60 trees together with higher infiltration capacities of the soils can have a delaying effect on stream 61 response, and pre-event water dominates the stormflow (Buttle, 1994; Klaus and McDonnell, 62 2013;Roa-García and Weiler, 2010). Roa-García and Weiler (2010) observed higher pre-event 63…”
Section: Introduction 29mentioning
confidence: 99%
“…This development has made it possible to investigate more 49 catchments or events. Few early IHS studies compared different catchments (Rodhe, 1987) and 50 only recently has IHS been used to compare neighboring headwaters (Laudon et al, 2007; Onda 51 et al, 2006) and/or many events (Hrachowitz et al, 2011; James and Roulet, 2009; Lyon et al, 52 2008;McGlynn et al, 2004;Roa-García and Weiler, 2010; Segura et al, 2012). Several of these 53 runoff generation studies found a more variable event and pre-event water contribution, contrary 54 to the presumed dominance in pre-event water found in the single headwater studies.…”
mentioning
confidence: 99%
“…Most case studies in tropical montane areas are from Latin America (e.g. Correa et al, 2017;Crespo et al, 2012;20 Mosquera et al, 2016b;Roa-García and Weiler, 2010;Timbe et al, 2014;Windhorst et al, 2014), whereas no data is available from African tropical montane catchments.…”
Section: Stable Water Isotopes ( 2 Hmentioning
confidence: 99%
“…Several distribution types have been used in catchment studies, including the dispersion model (Kirchner et al, 2001;McGlynn et al, 8 2003;McGuire et al, 2002), the piston flow model (McGlynn et al, 2003), and exponentialpiston flow (Maloszewski and Zuber, 1996;McGlynn et al, 2003;McGuire et al, 2002;Timbe et al, 2014). The exponential distribution has been the most widely used (more than 60% of the studies in several recent reviews; McGuire and McDonnell, 2006;Mueller et al, 2013;Roa-Garcia and Weiler, 2010;Seeger and Weiler, 2014), though more recently, the gamma function has been recognized as more conceptually and mathematically suitable to represent catchment behaviour and mixing processes due to its short breakthrough time and long tail (Birkel et al, 2012;Dunn et al, 2010;Heidbüchel et al, 2012;Hrachowitz, 2011;Hrachowitz et al, 2010;Kirchner et al, 2001Kirchner et al, , 2000Soulsby et al, 2011).…”
Section: Time Distribution Terms and Conceptsmentioning
confidence: 99%